THE CHANGING OF SANTRI’s PREFERENCE TOWARDS STUDIES AND PROFESSIONS: A Case Study at Pondok Pesantren Alhikmah 2 Brebes, Central Java - Hayyadin Ode (Balai Penelitian dan Pengembangan Agama Makassar, 2017)
This research aimed to figure out the santri’s preference toward studies and professions in which conduct study at pesantren. Common perceived and stated also at Government Ordinancenumber 55, 2007, that pesantren purposes was to reproduce Islamic scholar (ulama). However, through this study, it proved that not all santri wanted to be ulama, most of them wanted to be a scientist. This study was a case study, conducted in 2015 at Pesantren Alhikmah2 Brebes. Data collected using questionnaire, interview, and document. Those all derived from santris, Kyais, and teachers (asatidz). The research concluded as showed from questionnaire that santri’s preferences toward study has gotten changing to general subject matters instead of religious subject matters; and the santri’s professions and jobspreference has gotten changing to the jobs and professions that based on general subject matter, instead of choose to be ulama (Islamic scholar) most of santri wanted to be scientists, or researchers, or doctors as well as athlete.